Doing things the right way : Dene traditional justice in Lac La Martre, N.W.T. - Ryan, Joan, 1932- (University of Calgary Press, 1995)
"By exposing the very different values and legal systems of the Dene and non-Dene, this books sets the framework for the possibility of a Dene-controlled and culturally appropriate justice system ... [is] of value to those interested in native self-government, constitutional rights, and aboriginal law, as well as to all those involved with First Nations peoples."--Back cover